THE EFFECT OF REALISTIC MATHEMATICS APPROACH (PMR) ON MATHEMATICS UNDERSTANDING OF ELEMENTARY SCHOOL STUDENTS ON ONLINE LEARNING - Rahmawati, Dea; Irawati, Riana; Maulana, Maulana (Jurnal Pena Ilmiah, 2021)
This research was conducted on the basis of the importance of students having mathematical understanding at the elementary school level to improve higher mathematical abilities. Realistic Mathematics Approach (PMR) is one option that can be used to improve students' mathematical understanding in online learning. The research method used is descriptive quantitative with a pre-experiment one group pretest-posttest design. The research population is all fifth grade elementary school students in Jatinunggal District, Sumedang Regency. Meanwhile, the research sample is SDN Cisambeng. The instruments used in this research are mathematical understanding test questions, student response questionnaires, teacher and student performance observation sheets and interviews with four samples of parents. Based on the results of learning during three meetings, it shows that: 1) Realistic Mathematics Approach (PMR) has a significant positive influence on students' mathematical understanding of online learning through whatsapp groups. The magnitude of the change (gain) in the results of the pretest and posttest was 0.49 with a moderate interpretation; 2) The implementation of learning with PMR in online learning is going well even though there are some obstacles faced. The biggest obstacles in learning activities are students who do not master the basic skills of multiplication and division as well as unstable network problems. The lack of independence in student learning causes online learning to still have to be accompanied by parents and be guided directly.